BAGAIMANA MINAT MAHASISWA TERHADAP PEMBELIAN PRODUK DI MEDIA SOSIAL - Tiara Arsilla; Riza Wandriyani; Amalia Kusuma Mafazi; Nur Anisa; Budiandru Budiandru (Bajang Institute, 2023)
This research was conducted by students, this study aims to determine the effect of social media on consumer buying interest. This research was conducted using quantitative data, data collection in this study used a questionnaire containing 10 questions and was distributed to 41 respondents who had made a purchase at any online shop at least once. The results of the study show that there is a very strong and significant correlation between social media and consumer buying interest in college students. 97.6%. Respondents agree that online applications are very helpful in purchasing products. The reason is because it makes it easier for them to find goods without having to leave the house, just by using their cellphone and the online application, they can search for goods and buy them.